Job Search and Impatience - DellaVigna, Stefano; Paserman, M. Daniele (Journal of Labor Economics, 2005)
How does impatience affect job search? More impatient workers search less intensively and set a lower reservation wage. The effect on the exit rate from unemployment is unclear. In this paper we show that, if agents have exponential time preferences, the reservation wage effect dominates for sufficiently patient individuals, so increases in impatience lead to higher exit rates. The opposite is true for agents with hyperbolic time preferences: more impatient workers search less and exit unemployment later. Using two large longitudinal data sets, we find that various measures of impatience are negatively correlated with search effort and the exit rate from unemployment, and are orthogonal to reservation wages. Overall, impatience has a large effect on job search outcomes in the direction predicted by the hyperbolic discounting model.